Taxes and the Structure of Japanese Firms: The Hidden Aspects of Income Taxation - Hideki Kanda (Washington University Law Quarterly, 1996)
This Article addresses the influence income taxation has had on Japanese firms.
Keywords: Corporate governance – Japan; Corporations – Taxation